ECG Imaging of Ventricular Activity in Clinical Applications - Schulze, Walther H. W. (KIT Scientific Publishing, 2015)
ECG imaging was performed in humans to reconstruct ventricular activation patterns and localize their excitation origins. The precision of the non-invasive reconstructions was evaluated against invasive measurements and found to be in line with the state-of-the-art literature. Statistics were produced for various excitation origins and reveal the beat-to-beat robustness of the imaging method.
English
Keywords: inverses Problem; klinische Studieinverse problem of electrocardiography; clinical study; ECG imaging; EKG-Bildgebung